Hydrogen Bonding - New Insights - Grabowski, Slawomir (Challenges and Advances in Computational Chemistry and Physics,, 2006)
Hydrogen Bonding - New Insights Slawomir J. Grabowski Hydrogen Bonding - New Insights is an extensive text which takes numerous examples from experimental studies and uses these to illustrate theoretical investigations to allow a greater understanding of hydrogen bonding phenomenon. The most important topics in recent studies are considered including: Intra-molecular H-bonds Differences between H-bond and van der Waals interactions from one side and covalent bonds from the other Bader theory to analyze H-bonding Influence of weak H-bonds upon structure and function of biological molecules H-bonds in crystal structures With contributions from some of the foremost experts in this field this volume provides an invaluable resource for all members of the academic community looking for a comprehensive text on hydrogen bonding. It will be of particular interest to physical and theoretical chemists, spectroscopists, crystallographers and those involved with chemical physics.